Teleological Foundation of Islamic Education: A Thematic Quranic Interpretation of Surat Al-Dhariyat (51:56) - Jemmy Harto; Umdatul Hasanah; Fitri Hilmiyati; Deni Iriadi; Niampa Harouna (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
This study aims to analyze the concept of human creation in Sūrat al-Dhāriyāt (Qurʾān 51:56) and examine its implications for the philosophical foundation of Islamic education. The research employs a thematic Qurʾānic interpretation approach by analyzing classical and contemporary exegetical works, including - those of al-Ṭabarī and Ibn Kathīr, and relating them to contemporary discussions in Islamic educational thought. The findings indicate that the Qurʾānic concept of worship extends beyond ritual practices and encompasses a holistic orientation of human life toward devotion to God . From this perspective, the ultimate purpose of Islamic education is not merely intellectual development but the cultivation of individuals characterized by spiritual consciousness, intellectual competence, and ethical responsibility. This study proposes a teleological framework of Islamic education in which the purpose of education is derived from the existential purpose of human creation as servants of God. The framework highlights the integration of spiritual, intellectual, and moral dimensions within Islamic educational philosophy and offers a Qurʾānic foundation for contemporary discussions on the objectives of Islamic education.